2014
DOI: 10.1007/978-3-319-09767-1_7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coupling in Human-Virtual Agent Body Interaction

Abstract: Abstract. This paper presents a study of the dynamic coupling between a user and a virtual character during body interaction. Coupling is directly linked with other dimensions, such as co-presence, engagement, and believability, and was measured in an experiment that allowed users to describe their subjective feelings about those dimensions of interest. The experiment was based on a theatrical game involving the imitation of slow upper-body movements and the proposal of new movements by the user and virtual ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…The efforts made by both the autonomous agent and the WOz to adapt their behavior to that shown by the subject were not easily perceived and improved just a little the feeling of the interaction in condition SensitiveCoach. This confirms a similar result we obtained in the previous evaluation [2].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The efforts made by both the autonomous agent and the WOz to adapt their behavior to that shown by the subject were not easily perceived and improved just a little the feeling of the interaction in condition SensitiveCoach. This confirms a similar result we obtained in the previous evaluation [2].…”
Section: Discussionsupporting
confidence: 93%
“…The role of the interaction itself is rarely studied in terms of co-presence (experiments often consist in evaluating an agent standing in its virtual environment without interacting with it) and we consider that it is important and maybe crucial to favor the feeling of this property. For instance, we conducted an evaluation in [2] and showed that the effort produced by the human to maintain a sensorimotor coupling with an interactive virtual agent improves effectively the feeling of co-presence. Nonetheless, in this previous study, the agent was not controlled by an autonomous decision model but by a WOz.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the running state of the interaction we use the concept of coupling. Coupling is defined as the continuous mutual influence between two individuals [16]. It possesses the capability to resist to disturbances, and compensates them by making the interaction evolve.…”
Section: Principles: Aliveness Metaphor and Couplingmentioning
confidence: 99%
“…This definition is recursive since coupling exists because of the interactants' effort to "recover" it as its quality decreases. In [16] this effort is considered as an explanation of the improvement of the feeling of co-presence and engagement. Interactants measure coupling unconsciously and unconsciously they regulate it.…”
Section: Principles: Aliveness Metaphor and Couplingmentioning
confidence: 99%